Kontribusi Pemikiran Syed Sheikh Al-Hadi dalam Penguatan Pendidikan Perempuan di Dunia Melayu - Puspita Sari, Khovifah; Amelina, Naila; Abdurrahmansyah, Abdurrahmansyah; Fauzi, Muhammad (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2026)
This study examines the relevance of Syed Sheikh Ahmad al Hadi's thought to women's education in a contemporary context. Using a qualitative literature study approach with a historical-philosophical framework and content analysis techniques, this study analyzes al Hadi's primary works (novels, articles on Al Imam) and related secondary literature to identify key ideas and their relevance today. The analysis reveals three themes: women's education as a foundation for generation formation, a critique of patriarchal customs that reduce women's roles, and the use of literary media as a tool for pedagogical and communicative reform. Al Hadi's thought is considered to remain normatively and practically relevant, but needs to be recontextualized to 21st-century competencies such as digital literacy, critical thinking, and economic empowerment, and supported by supporting policies such as early childhood education services and gender-responsive leave policies. This study is primarily a literature study, so its limitations lie in empirical verification; further research is highly recommended. These findings contribute to the discourse of Malay Islamic modernism by highlighting the pedagogical and gender dimensions of al Hadi's reformist project and offering implementation directions for inclusive and sustainable educational reform.